Social Dimensions of Sustainable Development Goals in Asian Countries: Visual Dynamic Research Mapping - Andik Pratama; Juwita Purnami Restu Suwondo; Abdul Rahim Ridzuan; Riska Aprilia (Department of Development Economics, Universitas Sriwijaya, 2025)
As the 2030 deadline for the United Nations’ Sustainable Development Goals (SDGs) approaches, developing Asian nations face critical challenges in balancing economic expansion with the